Primary MALT-tracheal lymphoma: case report - O. V. Pikin; L. V. Telegina; I. B. Kaplanskaya; N. V. Kuteneva; V. V. Barmin; D. V. Semikina (Сибирский онкологический журнал, 2022)
Background. Tracheal cancer accounts 2 % of all upper respiratory tract cancers, with the incidence of 0.1 cases per 100,000 people per year. Primary tracheal MALT-lymphoma is extremely rare, and therefore there is no clearly established approach to the treatment of this disease. There are several effective positions regarding the choice of therapy. This article discusses the feasibility of endoscopic surgical treatment of primary tracheal lymphoma. The review of the literature presents current data on the epidemiology, etiopathogenesis, clinical features and treatment strategy for this disease.Description of the clinical case. A 72-year-old patient was admitted to the Thoracic Surgical Department of the P.A. Hertzen Cancer Research Center with complaints of shortness of breath with moderate physical exertion and dry cough. The examination revealed a tumor in the upper third of the trachea showing an exophytic growth, and grade I–III tracheal stenosis. To restore the lumen of the trachea and prevent complications, the endoscopic resection of the exophytic part of the tumor was performed. Histological and immunohistochemical studies revealed MALT-lymphoma of the trachea. Taking into consideration the indolent form of lymphoma, small size of the tumor, patient’s age and comorbidity, there were no indications for systemic anticancer therapy. The patient was recommended to be followed up. The patient is alive with no evidence of disease recurrence.Conclusion. This case report demonstrates the feasibility of performing organ-preserving endoscopic surgery in the patient with primary tracheal MALT-lymphoma. Taking into consideration the exophytic form of the tumor growth, endoscopic surgery made it possible to avoid unnecessary open tracheal resection, thus signifcantly improving the quality of life of the patient.